A Review of the Potential Benefits of Plants Producing Berries in Skin Disorders - Stefano Piazza; Marco Fumagalli; Saba Khalilpour; Giulia Martinelli; Andrea Magnavacca; Mario Dell'Agli; Enrico Sangiovanni (MDPI AG, 2020)
During the last 30 years, berries have gained great attention as functional food against several risk factors in chronic diseases. The number of related publications on Pubmed rose from 1000 items in 1990 to more than 11,000 in 2019. Despite the fact that a common and clear definition of "berries" is not shared among different scientific areas, the phytochemical pattern of these fruits is mainly characterized by anthocyanins, flavanols, flavonols, and tannins, which showed antioxidant and anti-inflammatory properties in humans. Skin insults, like wounds, UV rays, and excessive inflammatory responses, may lead to chronic dermatological disorders, conditions often characterized by long-term treatments. The application of berries for skin protection is sustained by long traditional use, but many observations still require a clear pharmacological validation. This review summarizes the scientific evidence, published on EMBASE, MEDLINE, and Scholar, to identify extraction methods, way of administration, dose, and mechanism of action of berries for potential dermatological treatments. Promising in vitro and in vivo evidence of Punica granatum L. and Vitis vinifera L. supports wound healing and photoprotection, while Schisandra chinensis (Turcz.) Baill. and Vaccinium spp. showed clear immunomodulatory effects. Oral or topical administrations of these berries justify the evaluation of new translational studies to validate their efficacy in humans.